THE EXPLOITATION OF ELICITING TECHNIQUES BY FOURTH-YEAR STUDENTS IN THEIR TEACHING PRACTICUM AT ENGLISH DIVISION I, FACULTY OF ENGLISH LANGUAGE TEACHER EDUCATION, UNIVERSITY OF LANGUAGES AND INTERNATIONAL STUDIES – VIETNAM NATIONAL UNIVERSITY - Nguyễn, Thanh Thủy (2020)
In the language teaching context, eliciting is praised as an effective technique, from which both teachers and students can benefit. It is believed to increase student talking time, maintain student attention, draw on what students already know or partly know, provide weaker students with opportunities to participate in class and motivate student to learn (Doff, 1988; Ur, 1996). Therefore, using eliciting techniques effectively is of great importance to teachers in general and to student-teachers in particular. Attempting to investigate the student-teachers’ exploitation of elicitation during practicum at university level, the current research aimed at investigating how the student-teachers from the Faculty of English Teacher Education (FELTE), University of Languages and International Studies (ULIS) used eliciting techniques during their practicum at English Division I, FELTE. Specifically, it explored these student-teachers’ perceptions of the necessity of eliciting techniques in language teaching together with the frequency of using each technique. Besides, the study discovered the student-teachers’ and first-year students’ evaluation of the student-teachers’ elicitation. Also, it found out the student-teachers’ difficulties when using these techniques in class and their suggested solutions to such difficulties. Data for the study were collected, firstly, by means of questionnaires with the participation of 26 student-teachers and 189 first-year mainstream students at FELTE. In addition, observing lessons of nine student-teachers and interviewing them helped provided valuable data for the study.